Produktivitas kinerja Pegawai Negeri Sipil di Kota Bitung - Lumingkewas, Elvis; Supit, Brain Fransisco; Masengi, Evi Elvira (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was conducted at the Girian District Office, Bitung City with the aim of analyzing the productivity of civil servant performance from the aspects of Attitude, Ability and Work Spirit as well as analyzing what obstacles are faced in preparing or creating employee performance targets. The method used is a qualitative research method. The results of this study show that 1) in terms of attitude, the performance of district staff is good and they are able to communicate well with the community; 2) In terms of efficiency, the performance of district staff remains low; 3) The performance of district employees remains the worst in terms of work ethics. The factors hindering the performance of the staff of Gillian District Office in Bitung City are: 1) lack of motivation to work, which may affect community participation in community activities; 2) County employees do not receive training or development so that they do not know what type of work they will be required to do when appointed as county employees; 3) The average age of district employees is 50 years old; 4) Existing regulations change very quickly; 5) Technical bodies still provide minimal information on the latest regulations.